Demystifying the "Victimized State": A Civil–Military Crisis in Waiting?. (January 2017) - McGarry, Ross
The purpose of this article is to illustrate prescient issues relating to current and ex-military communities in the United Kingdom who have featured heavily within the policy arena over the past decade in relation to several key areas of importance. It will be illustrated how this population becomes visible within the public imagination (via military losses), how discourses relating to the harms they experience are structured and articulated within political and policy domains (particularly in relation to mental health) via "state talk" (qua Sim), and what the potential social consequences are for politically rendering an unproblematized populist view of current and ex-military communities (i.e., pending crises). This argument is made with the express intention of reengaging critical recognition of the distancing of the military institution from the physical and psychological vulnerability of those who have participated in war and military environments. This is an argument returned to pertinence from the recent publication of the Chilcot Inquiry into British involvement in the Iraq war.